Pengaruh Persentase Biodiesel Minyak Nyamplung – Solar terhadap Karakteristik Pembakaran Droplet - Udin, Misbach; Yuliati, Lilis; Novareza, Oyong (Jurnal Rekayasa Mesin, 2017)
The aim of this research is to investigate the effect of biodiesel percentage on the droplet combustion characteristic of calophyllum inophyllum biodiesel-diesel fuel blended. The combustion characteristic included ignition delay time, flame visualization, burning rate, and flame temperature. Testing was conducted using fuel blended with biodiesel percentage of 0%, 10%, 30%, 50% and 100%. The fuel was dripped and shaped a droplet that placed on the tip of thermocouple junction and ignited using a heater. The result shown that the ignition delay time increase with increasing biodiesel percentage due to its high flash point temperature and low volatility. Furthermore, burning rate and flame temperature increase with the increasing biodiesel percentage in the blended. These phenomena related to more microexplosion occurrence in the droplet combustion of fuel blended with higher biodiesel content. The last result shown that combustion of diesel fuel droplet has the highest flame dimension, related to its low burning rate and faster vapor diffusion rate.Â